Socio-Ecological System Implications of Organizational Resilience - José G. Vargas-Hernández; M. C. Omar C. Vargas-González (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This paper aims to direct the socio-ecological system as a construct of organizational resilience able to include research to create a coherent and comprehensive analysis of the implications of uncertainty, complexity, discontinuity, and adversity. The analysis departs from the development of conceptualizations, definitions, methods, functions, operations, assessments, and measures. The methodology employed is based on transdisciplinary approaches to a qualitative and reflective analysis of the theoretical and empirical literature review. It is concluded that an integrated approach to organizational resilience must consider a socio-ecological system to assess the environmental implications of uncertainty, complexity, discontinuity, and adversity as a source of bouncing back and forward from organizational crises.